Pengaruh Celebrity Endorser dan Brand Image terhadap Keputusan Pembelian Produk Fashion pada Media Sosial Instagram - Allicya Willma Hillary (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In the modern era, the increase in fashion business people  in Indonesia who use Instagram as a means of promotion raises a lot of competition. Thus, business people must be careful in choosing celebrity endorsers to attract consumers.  One celebrity endorser who is on the rise in popularity due to the uniqueness  of his endorsement content is Fadil Jaidi. This makes  an Indonesian fashion brand called M231 entrust Fadil Jaidi to endorse   its fashion products. Fadil Jaidi is expected to help strengthen consumers' memories of the M231 brand  image which always revolves around elegant, casual, and modern impressions. Therefore, this study aims to prove the influence  of celebrity endorser Fadil Jaidi and brand image on  the purchase decision of  M231 fashion products on Instagram social media. This study used data collection techniques using survey methods, and sampling techniques using purposive sampling by distributing questionnaires to 61 respondents. The results proved that  celebrity endorser Fadil Jaidi had a positive and significant influence on the purchase decision of M231 fashion products on Instagram social media, brand image  did not have a significant effect on the purchase decision of  M231 fashion products on Instagram social media,  celebrity endorser Fadil Jaidi and  brand image  together influence the purchase decision of  M231 fashion products on Instagram social media.